The interplay between cell death and inflammation - Henry, Conor Maurice (Trinity College (Dublin, Ireland). Department of Genetics, 2015)
The connection between cell death and inflammation is an ancient one, first documented in the first century AD by the roman physician Galen. Cell death, as a consequence of tissue injury or infection, is a potent and universal stimulator of inflammation. This work sought to investigate two major aspects of how dying cells under different contexts might interact with the immune system. First, we investigated a role of the pro-apoptotic molecule TRAIL, as an inducer of inflammatory signalling, and explored the implications for the immune system in deciphering this mode of cell death. Second, we discovered the proteases responsible for the proteolysis and activation of IL-36 cytokines; members of the IL-1 cytokine family which represent key endogenous danger signals that alert the immune system in the event of necrotic cell death.
Keywords: Genetics, Ph.D.; Ph.D. Trinity College Dublin